2015
DOI: 10.1111/vde.12206
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a third feline Demodex species through partial sequencing of the 16S rDNA and frequency of Demodex species in 74 cats using a PCR assay

Abstract: Three Demodex species can be found in cats, because the third unnamed Demodex species is likely to be a distinct species. Apart from D. cati and D. gatoi, DNA from D. canis, D. folliculorum and D. brevis was found on feline skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 19 publications
4
18
0
6
Order By: Relevance
“…felis according to their host (cat), the 16S rRNA gene clustered Demodex mites in cats with dogs and humans. Ferreira et al [5] and Frank et al [14] found similar results using 16S rDNA. There are no previously published results for cats using the 18S rRNA gene.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…felis according to their host (cat), the 16S rRNA gene clustered Demodex mites in cats with dogs and humans. Ferreira et al [5] and Frank et al [14] found similar results using 16S rDNA. There are no previously published results for cats using the 18S rRNA gene.…”
Section: Discussionsupporting
confidence: 56%
“…D . canis also have been found in cats [5,15,16]. All these mammals are directly related to human activities (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations